A polymer-coated nanoparticle and a composite nanoemulsion and macroemulsion
By using polymer-coated nanoparticles and metal ions to combine, the problem of difficulty and high cost of synthesis of Pickering emulsions is solved, and the effect of stabilizing nano droplets and large emulsions in harsh environments is achieved.
Patent Information
- Application Number
- CN202110167224.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-07
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-02-07
AI Technical Summary
The prior art has problems such as difficult, complicated steps and high cost when synthesizing Pickering emulsions. Especially in high temperature, high pressure and high salt environments, it is difficult for traditional methods to stabilize nano droplets.
Polymer-coated nanoparticles or surfactants are used to combine metal ions as emulsifiers to form cage-shaped structures to grow nanoparticles through polymer self-assembly to form stable nanodroplets, and use these nanodroplets to stabilize a larger emulsion system.
It realizes stabilization of nano droplets and large emulsions under high temperature, high pressure and high salt environments, reducing the cost and complexity of traditional emulsion production, and improving the stability and specific surface area of the emulsion.
Smart Images

Figure CN114907576B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano composite materials, and in particular relates to polymer-coated nano particles and composite nano emulsions and macro emulsions. Background Art
[0002] An emulsion is a heterogeneous system consisting of two or more immiscible phases, at least one of which is dispersed in the form of droplets in the other continuous phase liquid. Two liquids, such as oil and water, can form either an oil-in-water (O / W) emulsion, in which the oil is the dispersed phase, or an oil-in-water emulsion (W / O), in which the water is the dispersed phase. By mixing these two liquids, a variety of emulsions can also be formed, including "oil-in-water (O / W / O)" and "water-in-oil-in-water (W / O / W)" emulsions.
[0003] Emulsions can be divided into macroemulsions, nanoemulsions and microemulsions according to particle size and properties. Traditional macroemulsions are easily formed by adding low concentrations of surfactants or surfactant polymers to reduce the surface tension between the dispersed phase and the continuous phase. Surfactants are amphiphilic and are widely used as emulsifiers. They have a strong adsorption effect on the oil-water interface. The hydrophobic group points to the oil phase and the hydrophilic group points to the water phase, so that the interfacial energy is reduced and the expansion and coalescence of the droplets are hindered. These surfactants can be non-ionic, anionic, cationic or zwitterionic surfactants. Similarly, surfactant polymers with amphiphilic properties have been proven to be effective stabilizers because the chains are amphiphilic and can effectively reduce the oil-water interfacial tension and prevent the emulsion from destabilizing. For example, in the patent US2008 / 0250701A1, it is described that succinic acid diester polymers can be used to prepare oil-in-water macroemulsions. The polymer contains a large hydrocarbon group connected to two hydrophilic alkyl oxygen chains through two ester bonds, and the molecular weight ranges from 500 to 1200.
[0004] An alternative to surfactants and surfactant polymers to form macroemulsions is to use solid particles to form emulsions, which are called Pickering emulsions. Compared with traditional emulsions, Pickering emulsions can maintain long-term stability because solid particles can reside at the liquid-liquid interface and form a shell around the droplets, providing a strong mechanical barrier to droplet aggregation. In addition, due to the reduced use of surfactants, Pickering emulsions have lower cytotoxicity and better biocompatibility than traditional emulsions. Therefore, Pickering emulsions are receiving widespread attention from industries such as petroleum, biopharmaceuticals, and food. According to the Pickering emulsion theory, there are two key factors in the formation of stable emulsions: first, the surface coverage should be high enough to make the emulsion stable for a long time. This requires that the particles should have close to complete surface coverage on the droplet surface and have a sufficiently dense particle layer. At this stage, the interaction between nanoparticles at the interface is dominated by gravity, forming a coherent monolayer with significant mechanical strength to prevent aggregation between droplets. Although Vignati et al. reported that the particle surface coverage of droplets can be as low as 5% (Vignati et al., 2003), it is generally believed that in order to obtain a stable emulsion, the particle surface coverage should be no less than 29%, and the particles need to be cross-linked to form a gel structure (Midmore, 1998). Secondly, the partial wettability of the emulsifier is another important factor affecting the stability and type of the emulsion. In order to achieve interfacial adsorption, the particle surface must have both hydrophilic and lipophilic groups. In order to regulate the wettability of the surface of solid particles, various methods have been used to adjust the surface properties of the particles. For example, the surface of rigid particles can be modified by non-covalent adsorption or covalent linkage of surfactants, polymers and small molecules to selectively change wettability and monodispersity. Yoon et al. previously used Fe 2+ and Fe 3+Iron oxide nanoparticles were synthesized by ion coprecipitation, and then the synthesized nanoparticles were simply mixed with a copolymer of sulfonated polystyrene and malonic acid (PSS-alt-MA) polymer. Their research and subsequent studies found that the PSS-alt-MA iron oxide nanoparticles synthesized by this simple adsorption method cannot be stabilized in high salt solutions in the presence of divalent metal ions (such as calcium ions), and the non-covalently adsorbed polymer easily falls off the particle surface. In addition, this PSS-alt-MA iron oxide nanoparticle is a highly hydrophilic nanoparticle that does not have lipophilic and hydrophilic amphiphilicity and cannot be directly used as an emulsifier to stabilize the emulsion. Only by connecting each copolymer-adsorbed iron oxide nanoparticle with 1,6-hexanediamine and 1-ethyl-3-(3-dimethylaminopropyl) hydrochloride carboxylic acid diimide crosslinkers to enhance its hydrophobicity can the emulsion be stabilized. Moreover, due to weak gelation, PSS-alt-MA iron oxide nanoparticles are not stable in API solutions (8wt% sodium chloride + 2wt% calcium chloride) in the presence of divalent metal ions (Yoon et al., 2011; Bargaria et al., 2013). Although Bargaria et al., 2013 found that a polysulfonated copolymer (2-acrylamidopropanesulfonate-co-acrylic acid) (AMPS-co-AA) weakly binds calcium ions, which can stabilize iron oxide nanoparticles in high-temperature, high-sodium and high-calcium API saline solutions (8wt% sodium chloride + 2wt% calcium chloride), and can resist extreme dilution and prevent the polymer from falling off the nanoparticles (Iqbal et al., 2017). However, the production of such nanoparticles requires a cumbersome and expensive covalent linking process to allow the entire nanoparticle to be encapsulated by the polymer. For example, in order to achieve complete encapsulation of iron oxide nanoparticles by polymers, at least three steps are required: first, the iron oxide nanoparticles synthesized by the coprecipitation method are placed in tetraethoxysilane so that the surface of the nanoparticles is encapsulated by silicon; secondly, the silicon-encapsulated iron oxide nanoparticles are placed in 3-aminopropyltriethoxysilane for surface amination; finally, the amination and silicon-encapsulated iron oxide nanoparticles are completely encapsulated with 2-acrylamide-2-methylpropane sulfonic acid and acrylic acid copolymer. Obviously, this method of achieving full encapsulation of nanoparticles by covalent connection requires cumbersome steps and is difficult to apply to large-scale production processes. Therefore, there is an urgent need to invent a simple method for encapsulating nanoparticles so that the nanoparticles can withstand high temperature, high pressure and high salt environments underground.
[0005] Compared with macroemulsions and microemulsions, nanoemulsions have droplet diameters of about 20-500 nanometers. They can be stably dispersed in solutions like nanoparticles, have high specific surface area per unit area, optically transparent appearance, and adjustable rheology, and are therefore widely used in drug delivery, food, cosmetics, drugs, and material synthesis. Nanoemulsions were first widely used in nanomedicine, but recently the concept of nanomedicine has also been applied to petroleum engineering. Compared with traditional surfactant flooding, nanodroplets synthesized using surfactants can significantly reduce the adsorption of surfactants on rock surfaces and increase tertiary oil recovery by about 8% (Nourafkan et al., 2018). However, nanoemulsions are extremely thermodynamically unstable systems that are very prone to Ostawald ripening, and small nanodroplets in nanoemulsions are prone to polymerization and growth. Traditional nanoemulsions can also be stabilized by surfactants and polymers. For example, patent US835763B92 describes a method that includes introducing a nanoemulsion into a wellbore containing a surfactant. However, at high temperature and high pressure, such oil-surfactant and polymer-stabilized nanoemulsions are prone to surfactant desorption and droplet aggregation and growth. In theory, if nanoparticles are used to stabilize the liquid-liquid interface, the Pickering nanoemulsion formed has higher stability. However, even with very fine nanoparticles, the synthesis of stable Pickering nanodroplets smaller than 500 nanometers remains a huge challenge. Kang et al. (2018) designed a method for synthesizing nanoscale Pickering nanoemulsions using water vapor condensation, but this method can only synthesize water-in-oil Pickering nanoemulsions. Saelices and Capron (2018) tried to use dextran nanoparticles to synthesize oil-in-water Pickering nanoemulsions. However, they found that it was difficult to synthesize Pickering nanoemulsions under normal pressure conditions, and only under high pressure conditions could water-in-oil Pickering nanoemulsions be synthesized.
[0006] Based on the difficulty, complicated steps and high cost of synthesizing Pickering emulsions, the current synthesis of large emulsions often requires high concentrations of surfactants and solid particles to remain at the oil-water interface to reduce surface tension to stabilize large oil droplets. It is of great significance to develop a simple and cost-effective method for synthesizing emulsions. Summary of the invention
[0007] Based on the defects of the above-mentioned prior art for synthesizing Pickering emulsions, a technical problem to be solved by the present invention is to provide a method for synthesizing emulsions, which uses polymer-coated nanoparticles or surfactants combined with metal ions as emulsifiers to stabilize nanodroplets, and then uses nanodroplets as emulsifiers to stabilize the emulsion and expand the surface area of the emulsion, thereby reducing the amount of nanoparticles and surfactants used to stabilize the emulsion and reducing the production cost of traditional emulsions.
[0008] The present invention provides a method for making stable nanoemulsions and micron macroemulsions using polymer-coated nanoparticles. Compared with the use of nanoparticles and surfactants alone, the nanodroplets provided by the present invention are much more efficient in stabilizing emulsions. The present invention also develops a method for polymer-coated nanoparticles: nanoparticles, especially iron oxide nanoparticles (5-150 nanometers), can be synthesized by a biomimetic mineralization method. First, the polymer is assembled to form a cage structure, and then the cage formed by the self-assembly of the polymer is used as the cage structure, and nanoparticles are formed inside the cage structure, so that the nanoparticles are completely coated with the polymer, and are not affected by high salt water, brine, elevated temperature or other harsh conditions, and do not require expensive and cumbersome chemical covalent bonding to coat the polymer molecules to the surface of the nanoparticles. The composition of the polymer can be adjusted according to the conditions of the target application, such as reservoir temperature, pressure and salinity. These coated nanoparticles and surfactants, especially in combination with multivalent metal cations, can form nanodroplets (diameter 100 to 600 nanometers) in the water phase that stabilize the oil phase. The nanodroplets in turn can stabilize the emulsion system with larger particle size (large oil droplets dispersed in the water phase).
[0009] The polymer-coated nanoparticles and surfactants provided by the present invention provide a new and simple method for preparing stable nanodroplets. Both nanodroplets and nanodroplet-stabilized macroemulsions have a wide range of applications, from drug delivery to enhanced in situ or in vivo imaging, to enhanced oil recovery and catalysis.
[0010] Specifically, in order to solve the above technical problems, the present invention provides the following technical solutions:
[0011] The first object of the present invention is to provide a polymer-coated nanoparticle, wherein the polymer self-assembles into a cage-like structure to coat the nanoparticle; the nanoparticle is an iron-containing metal oxide.
[0012] The polymer comprises sulfonic acid groups and carboxyl groups, and the sulfonic acid groups and carboxyl groups can be fully or partially converted into the form of salts, and the salts are potassium salts, sodium salts, and ammonium salts.
[0013] Further, the polymer is obtained by copolymerizing an unsaturated monomer containing a sulfonic acid group and an unsaturated monomer containing a carboxyl group; the unsaturated monomer containing a sulfonic acid group includes styrene sulfonate, methacrylic acid sulfonate, propylene sulfonate, vinyl sulfonate, butylene sulfonate, and 2-acrylamide-2-methylpropane sulfonate; the unsaturated monomer containing a carboxyl group is selected from maleic acid, acrylic acid, methacrylic acid, crotonic acid, 2-ethylacrylic acid, 2-pentenoic acid, 4-pentene, 2-octenoic acid, 3-vinylbenzoic acid, 4-vinylbenzoic acid, 10-undecenoic acid, erucic acid, brassinoic acid, palmitoleic acid, oleic acid, nervonic acid, linolenic acid, ricinoleic acid, 4-oxo-4-phenyl-2-butenoic acid, 2-bromoacrylic acid, 2-bromomethyl-acrylic acid, sorbic acid, itaconic acid, citraconic acid, fumaric acid, methylfumaric acid, mesaconic acid, 2-methylsuccinic acid, and mucofuric acid.
[0014] The molecular weight of the polymer is determined by the size and space of the cage structure. Generally, the molecular weight of the polymer is 1-3 million, preferably 1.5-2 million; or the number of repeating units of the polymer is 50-200, preferably 90-120.
[0015] Preferably, the polymer is a sodium salt of poly(4-styrenesulfonic acid-maleic acid copolymer), wherein the ratio of the sulfonate to the carboxyl group in the polymer is 1:2, and the molecular weight is 1.5-2 million.
[0016] The chemical structure of the metal oxide nanoparticles is Fe (3-x) M x O4(0≤x≤3) or Fe (2-x) M x O3 (0≤x≤2), wherein the M is selected from Mn, Cu, Zn, Ni, Gd or Co. The size of the metal oxide nanoparticles is 5-150 nm, preferably 10-20 nm.
[0017] Preferably, the metal oxide nanoparticles are Fe3O4, Fe 1.5 Co 1.5 O4.
[0018] The polymer-coated iron-containing metal oxide nanoparticles provided by the present invention, wherein the polymer can self-assemble to form a spherical cage-type structure with an inner diameter of about 10-40 nm. The metal oxide nanoparticles are approximately spherical or ellipsoidal, with a ratio of major axis to minor axis of 1 to 2. The polymer-coated iron-containing metal oxide nanoparticles can be stable in an aqueous solution with a pH of 3-11. The polymer-coated iron-containing metal oxide nanoparticles can withstand a high temperature of at least 90° C.; the weight ratio of the polymer to the iron oxide nanoparticles is 1-4.
[0019] The second object of the present invention is to provide a method for preparing the above-mentioned polymer-coated nanoparticles, comprising the following steps: a) allowing the polymer to self-assemble into a cage structure; b) adding metal salts and oxidants to grow nanoparticle crystals in the cavity of the cage structure formed by the polymer.
[0020] The conditions for the polymer to self-assemble into a cage structure are salt concentration of 0.05-1M halide salt, such as NaCl, KCl, preferably 0.1-0.2M, pH value of 3-10, preferably 5-8.5, more preferably 7-8.5; temperature of 45-90°C, preferably 50-60°C, more preferably 50-55°C; polymer concentration of 0.25-5mg / mL, preferably 1-2mg / mL. By controlling the ionic strength, pH value and temperature in the solution, the polymer can form cage structures of different sizes.
[0021] The synthetic nanoparticles are synthesized in a cage formed by a polymer, specifically, a metal salt and an oxidant are slowly added to the system respectively. The amount of metal salt added determines the particle size distribution of the nanoparticles. Theoretically, the amount of metal salt added is such that each polymer cage contains one nanoparticle, and a single nanoparticle in the cage has 1000-120000 metal atoms, preferably each polymer cage has 5000-10000 metal atoms.
[0022] The metal salt includes an iron salt. Optionally, a salt of a metal M may be added, and the metal M is selected from at least one of Mn, Cu, Zn, Ni, Gd, and Co. The anion of the salt is not particularly limited, such as a halide, sulfate, or nitrate. The iron salt is specifically selected from at least one of ammonium ferrous sulfate, ferrous chloride, ferrous sulfate, and ferrous nitrate. The salt of the metal M is preferably a halide, such as manganese chloride, copper chloride, or cobalt chloride.
[0023] The oxidant is not particularly limited, as long as it can oxidize low-valent salts of metals into high-valent salts, such as hydrogen peroxide.
[0024] The metal oxide nanoparticles and the oxidant are added in a molar ratio of metal salt to oxidant of 2-3:1.
[0025] The metal salt is added at a rate of 10-200 metal ions per minute per polymer in the system, preferably 80-120 metal ions per minute per polymer.
[0026] Preferably, after obtaining the polymer-coated nanoparticles, a purification step (c) is further performed: the synthesized magnetic nanoparticles are concentrated using a protein enrichment tube after centrifugation, the nanoparticles not generated inside the polymer cage are removed by centrifugation, and then high-concentration polymer-coated nanoparticles are obtained by concentration.
[0027] Further preferably, in order to ensure that each iron oxide nanoparticle is completely encapsulated by the polymer cage, the magnetic nanoparticles that are easy to aggregate or difficult to encapsulate are removed by centrifugation at a centrifugal force of 5000-20000g for 10-30 minutes, and the synthesized magnetic nanoparticles are concentrated to 20-50 mg / mL using a protein enrichment and concentration tube with a molecular weight cutoff of 100-200kD for storage and standby. After the polymer forms a cage structure, the nanoparticle resides in a separate self-assembled polymer cage cavity to protect the nanoparticle from damage by high-salt salt water, high temperature or other harsh conditions.
[0028] The third object of the present invention is to provide a composite nanoemulsion, comprising: a) a continuous phase; b) a discontinuous phase; c) a stabilizer; d) metal ions, wherein the stabilizer comprises the above-mentioned polymer-coated nanoparticles.
[0029] The particle size of the composite nanoemulsion is 20-1000 nm, preferably 100-600 nm.
[0030] The continuous phase is a polar solvent such as water, alcohol and nitrile. The polar alcohol and nitrile solvents are well known in the art, such as methanol, ethanol, isopropanol, butanol, propylene glycol, glycerol, butanediol, acetonitrile, propionitrile, etc. The polar solvent can be added alone or in the form of a solvent in a stabilizer solution.
[0031] The discontinuous phase is oil, such as unsaturated fatty acid, mineral oil, fatty oil, silicone oil, etc., which is incompatible with the continuous phase. The ratio of the volume of the discontinuous phase to the volume of the continuous phase is 0.15 to less than 1, preferably 0.18-0.3.
[0032] The polymer-coated nanoparticles can be used alone as a stabilizer. Preferably, the polymer-coated nanoparticles can be combined with metal ions so that they can more easily reach the oil-water interface.
[0033] The concentration of the polymer-coated nanoparticles in the nanoemulsion is 0.2-2 wt %, preferably 0.8-1.2 wt %.
[0034] Metal ions can be monovalent or polyvalent. + ,K + , Ca 2+ ,Co 2+ , Ni 2+ , Ba 2+ ,Mg 2+ ,Al 3+ , Cu 2+ The concentration of metal ions in the system is 0.1-0.3 M. Preferably, it is a divalent metal ion, such as Ca 2+ ,Co2 + , Ni 2+ , Ba 2+ ,Mg 2+ At least one of .
[0035] The polymer-coated nanoparticles can react with oil to form very small oil-phase nanodroplets with a particle size of less than 1000 nanometers. In this composite nanoemulsion system, the polymer-coated nanoparticles, metal ions and nanodroplets all play a role in stabilizing the emulsion.
[0036] A fourth object of the present invention is to provide a method for preparing the composite nanoemulsion, comprising the following steps:
[0037] A) adding a water phase, a stabilizer, metal ions and an oil phase and mixing them, wherein the stabilizer comprises the above-mentioned polymer-coated nanoparticles;
[0038] B) centrifugation to separate and take the middle layer of emulsion as the composite nanoemulsion.
[0039] Nanoemulsions can accumulate at the oil-water interface, and the oil and water content can be quantitatively assessed by optical or magnetic methods, where the optical method can be fluorescence or laser methods, and the magnetic method can be magnetic resonance, magnetoacoustic, electromagnetic, magnetic susceptibility or magnetization intensity methods.
[0040] Further preferably, the stabilizer can also be added with anionic surfactants and cationic surfactants, which are adsorbed on the nanodroplets, so that the nanodroplets can reduce the surface tension of the liquid-liquid interface and more effectively recover oil from the reservoir. The metal ions at the interface of the polymer-coated nanoparticles and the nanodroplets can react dynamically with the oil to form a nano- or micron-sized emulsion. Compared with the traditional Pickering emulsion, it is more effective to recover oil from the reservoir.
[0041] The fifth object of the present invention is to provide a macro emulsion, comprising a) a continuous phase, b) a discontinuous phase; c) a stabilizer, wherein the stabilizer comprises the composite nanoemulsion. The term "macro emulsion" corresponds to "microemulsion" or "nanoemulsion", and means that the size of the particles in the emulsion is in the size class of 10-100 μm, and its oil-water interface is covered with many composite nanoemulsions and microemulsions (1-10 μm), having an extremely high specific surface area.
[0042] The continuous phase is a polar solvent such as water, alcohol and nitrile. The polar alcohol and nitrile solvents are well known in the art, such as methanol, ethanol, isopropanol, butanol, propylene glycol, glycerol, butanediol, acetonitrile, propionitrile, etc. The polar solvent can be added alone or in the form of a solvent in a stabilizer solution.
[0043] The discontinuous phase is oil, such as unsaturated fatty acid, mineral oil, fatty oil, silicone oil, etc., which is incompatible with the continuous phase. The volume ratio of the discontinuous phase to the continuous phase is 0.5-3, preferably 1-2.
[0044] The polymer-coated nanoparticles provided by the present invention as stabilizers can provide multiple functions to stabilize the emulsion. First, the specific wetting properties of the polymer-coated nanoparticles themselves allow the nanoparticles to be adsorbed on the oil / water interface to form a single layer and / or multilayer film, thereby stabilizing the emulsion. Secondly, the metal ions can be combined with the functional groups of the polymer and attached to the nanodroplet interface together with the polymer-coated nanoparticles to play a stabilizing role; thirdly, the polymer-coated nanoparticles combined with the metal ions stabilize the oil-water interface and can form very small oil-phase nanodroplets with the oil and water. The nanodroplets can stabilize the oil-water interface of a larger size and further form micron droplets, that is, large emulsions. This ring-in-ring stabilization method, that is, the stabilizer provided by the present invention, stabilizes the large emulsion through the synergistic effect of polymer-coated nanoparticles, metal ions, and the formed nano / micro droplets, and the required concentration of polymer-coated nanoparticles is extremely low. Experiments have shown that at an extremely low concentration of 0.0002wt%, the polymer-coated nanoparticles provided by the present invention can form a stable large emulsion. Since the concentration required for forming a stable emulsion is extremely low, it has the advantage of low cost. At the same time, the method for stabilizing the emulsion is simple and easy to operate, which has industrial advantages.
[0045] A sixth object of the present invention is to provide a method for preparing the above-mentioned large emulsion, comprising the following steps:
[0046] The prepared composite nanoemulsion, the continuous phase and the discontinuous phase are uniformly mixed to obtain a macroemulsion.
[0047] A seventh object of the present invention is to provide uses of the composite nanoemulsion for drug delivery, in situ or in vivo imaging, displacement of residual petroleum or catalysis.
[0048] For example, when used to displace residual petroleum, compared with other oil-displacing agents, the Pickering composite nanoemulsion of the present invention can specifically adsorb on the oil-water interface of the residual oil and react to generate larger oil phase nanodroplets and micron droplets for displacement. At normal temperature and pressure, about 30% of the residual oil can be displaced.
[0049] Compared with other currently synthesized polymer iron oxide nanoparticles and Pickering emulsions, the technical solution of the present invention has the following advantages:
[0050] 1. The polymer-coated nanoparticles provided by the present invention can control the particle size distribution by adding different amounts of metal ions, such as the amount of iron, without the need for expensive and cumbersome chemical covalent linking of polymer molecules to the surface of the nanoparticles, and can withstand harsh conditions such as high salt and high temperature. The composition of the surface polymer can be adjusted according to the conditions of the target application.
[0051] Second, the polymer-coated nanoparticles of the present invention are synthesized in a cage and are strictly controlled by the cage, so they have the advantages of monodispersity, stable size distribution and shape, and controllable, and a single nanoparticle is well coated by the polymer. This eliminates the situation where the traditional method requires several steps to covalently link the nanoparticles with expensive cross-linking agents and polymers to obtain monodisperse nanoparticles that are stable under high salt conditions. Moreover, the synthesis process of the polymer-coated nanoparticles provided by the invention is simple. Using the polymer self-assembled cage as a nano-platform, it is only necessary to gradually add a certain amount of reaction solution according to the concentration of the polymer in the solution. Since this synthesis method is similar to biomineralization, it can be carried out at relatively low temperatures and pH values. This avoids the limitation of the traditional chemical synthesis method that requires the use of high temperatures and organic solvents to form nanoparticles with good shapes and high crystallinity.
[0052] Third, the inventors utilize the characteristics of completely hydrophilic polymer-coated nanoparticles or surfactants that can bind metal ions but are stable under high metal ion concentration conditions to form a method for forming an oil-in-water nanoemulsion under normal pressure conditions. These oil phase nanodroplets (diameter 20 to 600 nanometers) that can be stable in the water phase can continue to dynamically react with the oil and crosslink to stabilize the large emulsion by covering the surface with polymer-coated nanoparticles, surfactants and multivalent metal ions. This method of stabilizing a large emulsion by nanodroplets has not been reported yet. It not only greatly increases the specific surface area of the emulsion, but also greatly reduces the amount of solid particles or surfactants used, overcoming the limitation that conventional large emulsions require a large amount of solid particles or surfactants to be stable, and has a wide range of application value.
[0053] Fourth, the Pickering emulsion provided by the present invention can be formed into very fine nano droplets by adding electrolytes and metal ions, and these nano droplets can be further used to stabilize larger nano droplets to form complex nano emulsions and / or micro droplets. This greatly expands the specific surface area of the nano emulsion. It overcomes the necessity of traditional nano particles to adsorb or covalently link surfactants, polymers or small molecules to selectively change the wettability of nano particles. The Pickering nano emulsion is successfully synthesized by adsorbing polymer-coated nano particles and metal ions on the liquid-liquid interface. The polymer-coated nano particles can cross-link with each other at the interface to form a strong spatial mechanical barrier to prevent the aggregation and growth of oil phase nano droplets.
[0054] 5. Nanodroplets stabilized by polymer-coated nanoparticles can replace traditional nanoparticles, forming nanodroplets and microdroplets with larger specific surface area at the interface of large droplets to provide a spatial barrier. Since nanodroplets and microdroplets greatly increase the particle size and specific surface area of nanoparticles, the amount of nanoparticles required at the interface of large emulsions is greatly reduced to 0.002-0.1wt%. This is the minimum amount of nanoparticles reported so far.
[0055] 6. The polymer-coated nanoparticle-stabilized emulsion provided by the present invention is more stable than conventional Pickering emulsions and has a larger surface area. The large surface area means that this large emulsion has a wide range of applications in improving oil recovery and catalytic performance.
[0056] 7. The preparation method of the composite nanoemulsion provided by the present invention is simple. By regulating the metal ion composition and concentration, surfactant and oil phase components, a complex nanoemulsion composed of a mixture of extremely fine droplets of multiple different oil phase components can be synthesized. This complex nanoemulsion has an extremely high specific surface area, and contains polymer-coated nanoparticles, multiple metal ions or surfactants on the surface. It has broad application prospects in improving oil recovery or catalysis. At the same time, it is found that when using composite nanoemulsion to stabilize large emulsions, a lower concentration is required than nanoemulsion.
[0057] Eighth, the inventors also applied nanoemulsions and composite nanoemulsions to the detection and displacement of residual oil, and found that nanoemulsions and complex nanoemulsions can specifically gather at the oil-water interface of residual oil for quantitative detection and evaluation of the residual oil content. At the same time, it was found that nanoemulsions or complex nanoemulsions can dynamically react with participating oils and emulsify them, which has important application prospects in the future in improving oil recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1It shows that the poly(4-styrenesulfonic acid-maleic acid copolymer) sodium salt (PSS-co-MA) in Example 1 self-assembles to form a cage structure under different pH and temperature conditions. Figure 1 a-1c is the distribution of polymer hydrate particle size measured by dynamic light scattering; Figure 1 d-1j Negative staining transmission electron microscopy observation of cage-like structures formed at different temperatures.
[0059] Figure 2 The electron microscope photographs of the polymer-coated nanoparticles formed by loading different numbers of iron atoms (5000, 20000, 60000, 80000) into the PSS-co-MA cage by a biomimetic synthesis method in Example 2 are shown, as well as the particle size distribution and the ratio of the major and minor axes.
[0060] Figure 3 The biomimetic polymer PSS-co-MA coated iron oxide nanoparticles (PSS-co-MA) with different iron atom loadings synthesized in Example 2 are shown. 5000 、PSS-co-MA 20000 、PSS-co-MA 30000 、PSS-co-MA 60000 、PSS-co-MA 80000 ) by thermogravimetric analysis.
[0061] Figure 4 The polymer PSS-co-MA coated iron oxide nanoparticles (PSS-co-MA) with different iron atom loadings synthesized in Example 2 are shown. 20000 、PSS-co-MA 80000 ) stability between pH 3-11.
[0062] Figure 5 The polymer PSS-co-MA coated iron oxide nanoparticles synthesized by Example 2 were shown to be stable under high concentration saline (API solution: 8wt% NaCl+2wt% CaCl2) and high temperature conditions (90°C, 180°C).
[0063] Figure 6 The biomimetic polymer PSS-co-MA coated iron oxide nanoparticles (PSS-co-MA) with different iron atom loadings synthesized in Example 2 are shown. 5000 、PSS-co-MA 20000 ,PSS-co-MA 60000 、PSS-co-MA 80000 )Isothermal remanence (IRM) curve and demagnetization curve (DCD) were obtained at 5K.
[0064] Figure 7The biomimetic polymer PSS-co-MA coated iron oxide nanoparticles (PSS-co-MA 5000 、PSS-co-MA 20000 、PSS-co-MA 60000 、PSS-co-MA 80000 ) hysteresis loops at different temperatures.
[0065] Figure 8 The transmission electron microscopy image (a), particle size distribution (b), and electron microscope energy spectrum (c) of the polymer PSS-co-MA synthesized in Example 3 capped with cobalt-doped iron oxide nanoparticles are shown.
[0066] Fig. 9 The biomimetic polymer PSS-co-MA synthesized in Example 2 coated iron oxide nanoparticles (PSS-co-MA 5000 ) and the difference between the conventional ultrasonic chemical adsorption polymer PSS-co-MA coated iron oxide nanoparticles by comparative example.
[0067] Fig.10 The results show that the polymer-coated iron oxide nanoparticles (PSS-co-MA) synthesized in Example 2 under different NaCl concentrations 5000 The optical properties of the emulsion formed by mixing 0.1wt%) with dodecane are shown in Table 1. Fig.10 a) and microscope photographs ( Fig.10 b).
[0068] Fig.11 The results show that the polymer-coated iron oxide nanoparticles (PSS-co-MA) synthesized in Example 2 under different concentrations of CaCl2 5000 The optical properties of the emulsion formed by mixing 0.1wt%) with dodecane are shown in Table 1. Fig.11 a) and microscope photographs ( Fig.11 b).
[0069] Fig.12 It is shown in Example 4 that different concentrations of polymer PSS-co-MA 5000 Stability of nanoemulsions formed by mixing coated iron oxide nanoparticles with octadecene and 0.2 M calcium chloride after being stored for different days.
[0070] Fig.13 Two-dimensional and three-dimensional laser confocal microscopy, cryo-scanning electron microscopy, atomic force microscopy, and X-ray scanning transmission microscopy imaging of the nanoemulsion formed by Example 4 are shown.
[0071] Fig.14 The relationship between the hydrated particle size of the nanoemulsion formed in Example 4 and the storage time and temperature measured by dynamic light scattering is shown.
[0072] Fig.15 The results of Example 9 show that different low concentrations (0.001-0.01 wt%) of polymer-coated iron oxide nanoparticles (PSS-co-MA 5000 ) aqueous solution, polymer-coated iron oxide nanoparticles in salt solution (0.2 M CaCl2), polymer-coated iron oxide nanoparticles in aqueous solution stabilized nanodroplets, and nanodroplets in salt solution (0.2 M CaCl2) after storage at room temperature for 38 days.
[0073] Fig.16 It is shown that by Example 9, the polymer PSS-co-MA coated iron oxide nanoparticles (PSS-co-MA 5000 ) salt solution (0.2M CaCl2), nanodroplet water solution, and nanodroplet salt solution (0.2M CaCl2) emulsions.
[0074] Fig.17 Comparison of the polymer PSS-co-MA coated iron oxide nanoparticles (PSS-co-MA 5000 ) salt solution (0.2M CaCl2), nanodroplet water solution, and nanodroplet salt solution (0.2M CaCl2) after storage for 56 hours and 6 days.
[0075] Fig.18 The microstructure of the emulsion prepared from Example 9 with 0.01 wt% nanodroplet salt solution (0.2 M CaCl2) is shown.
[0076] Fig.19 Shown are the low-temperature scanning electron microscopy and energy dispersive spectroscopy (EDX) analysis images of the emulsion prepared by Example 9 and prepared from a nanodroplet salt solution (0.2 M CaCl2).
[0077] Fig. 20 Oil-in-water emulsions containing different metal cations prepared by Example 9 and Example 10 are shown.
[0078] Fig.21 The cryo-scanning electron microscopy (a), atomic force microscopy (b), oxygen edge X-ray scanning transmission microscopy (c), hydrated particle size distribution (d) and energy spectra (e, f) of the composite nanoemulsion prepared by Example 5 are shown.
[0079] Fig. 22 The cryo-scanning electron microscope images (a, c), size distribution (b), energy spectrum (d), atomic force microscope (e) and oxygen-edge, iron-edge and benzene ring-edge X-ray scanning transmission X-ray microscope images (fh) of the composite nanoemulsion prepared by Example 6 are shown.
[0080] Fig.23 (a, b) cryo-scanning electron microscope images, (c) atomic force microscope images and (d) structural schematic diagram of the water-in-oil composite nanoemulsion containing multiple oil components, multiple metal ions and cationic surfactants prepared by Example 7 are shown.
[0081] Fig.24 The cryo-scanning electron microscope image (a), atomic force microscope image (b) and structural schematic diagram (c) of the composite nanoemulsion containing anionic surfactant prepared by Example 8 are shown.
[0082] Fig.25 The photographs are shown after 48 hours of emulsion synthesis using different concentrations of water-in-oil composite nanoemulsions containing multiple oil components and multiple metal ions prepared in Example 11.
[0083] Fig.26 The three-dimensional micromodel (b) and the macroemulsion model (c) made by laser confocal microscopy and the two-dimensional displacement micromodel (a) and quartz sand according to Example 12 are shown. DETAILED DESCRIPTION
[0084] The polymer-coated nanoparticles of the present invention, and the composite nanoemulsion and macroemulsion formed therefrom are further explained with reference to specific embodiments below.
[0085] Unless otherwise specified, the reagents used in the embodiments of the present invention can be purchased commercially.
[0086] Example 1. Polymer self-assembly to form cage-like structure
[0087] The sodium salt of 4-styrenesulfonic acid-maleic acid copolymer (molecular weight of about 20,000, molar ratio of styrenesulfonic acid and maleic acid of 1:1) was prepared with 0.1M NaCl to a concentration of 1 mg / mL, and the pH of the solution was adjusted to pH 3, pH 5, pH 7, pH 8.5, and pH 9 with 0.01M NaOH and hydrochloric acid. The hydrated particle size of the polymer was measured under different pH and temperature conditions (25°C, 55°C, and 90°C) using dynamic light scattering. The results showed that only under pH 5-8.5 conditions, the polymer was able to maintain its secondary structure well, and the volume percentage hydrated particle size at 25°C was about 12nm ( Figure 1a). When heated to 55°C and 90°C under the conditions of a dynamic light scattering instrument, the polymer began to self-assemble to form a structure with a larger hydrated particle size. Since the dynamic light scattering measurement of hydrated particle size is easily affected by temperature and aggregation, in order to more intuitively observe the structure formed by polymer self-assembly, we heated the polymer to different temperatures under pH 7-8.5, and then took the polymer solution to observe the morphology of the polymer by negative staining with a transmission electron microscope. Finally, it was found that at 55°C, the polymer can self-assemble to form a monodisperse cage structure. The self-assembled polymer cage structure was determined using a single particle inductively coupled plasma mass spectrometer (ICP7900) to determine the content of sulfur isotopes in the polymer, and it was finally determined that the cage structure of the polymer was assembled from 96 monomers with a molecular weight of approximately 1,920,000.
[0088] Figure 1 a-1j shows that the sodium salt of poly(4-styrenesulfonic acid-maleic acid copolymer) (PSS-co-MA) in Example 1 self-assembles to form a cage structure under different pH and temperature conditions. (a) The particle size distribution of the hydrated polymer measured by dynamic light scattering at room temperature (25°C) found that the secondary structure of the polymer can only be formed under pH 5-8.5 conditions, while when the temperature rises to 55°C (b) and 90°C (c), the polymer forms a tertiary structure with a larger hydrated particle size. Since the hydrated particle size is easily affected by temperature and aggregation, (dj) we placed 1 mg / mL of the polymer in 0.1 m NaCl, pH 8.5 at different temperatures to form a cage structure for negative staining transmission electron microscopy observation. The experiment found that the polymer PSS-co-MA can self-assemble to form a cage structure under pH 8.5 and 55°C. The inner diameter of the cage cavity is approximately 13-40 nanometers, and the average inner diameter is 18.8±2.5nm.
[0089] Example 2. Preparation of polymer-coated iron oxide nanoparticles by biomimetic synthesis
[0090] All solutions were deoxygenated and placed in an anaerobic chamber. Ammonium ferrous sulfate (100 mM) and hydrogen peroxide (33.33 mM) solutions were prepared using anaerobic deionized water. In order to obtain a self-assembling polymer, 1 g of polystyrene sulfonate sodium-maleic acid copolymer (PSS-co-MA, molecular weight of about 20,000) polymer was dissolved in 1 L of 0.1 M NaCl solution until the final concentration was 1 mg / mL, and the pH value was adjusted to 8.5 with 0.5 M NaOH. The temperature was controlled at 55 ° C for 10 min by an electric heating mantle, so that the polymer began to self-assemble under the conditions of salt ion concentration, pH value and temperature to form a cage structure (each cage contains 96 monomers and the molecular weight is about 1920000). According to the molar number of polymer cages and the molar concentration of ammonium ferrous sulfate, it was calculated that by adding ammonium ferrous sulfate (100 mM) and hydrogen peroxide (33.34 mM) solutions at a rate of 80 iron atoms per minute per cage, theoretically about 5000, 20000, 60000, and 80000 iron atoms would be added to each cage, respectively, to form iron oxide (magnetite, Fe3O4) nanoparticles with different particle size distributions, namely PSS-co-MA 5000 、PSS-co-MA 20000 ,PSS-co-MA 60000 、PSS-co-MA 80000 To ensure that each iron oxide nanoparticle was completely encapsulated by the polymer cage, the magnetic nanoparticles that were easy to assemble or difficult to encapsulate were removed under a centrifugal force of 10,000 g, and the synthesized magnetic nanoparticles were concentrated using a 100 kD protein enrichment tube (amicon Ultra-12100 kda) to remove the free polymer and store it at 30 mg / mL. The iron content and polymer content in the nanoparticles were determined by inductively coupled plasma mass spectrometry (ICP-MS) and thermogravimetric analysis (TGA).
[0091] Figure 2 It is shown that in Example 2, different numbers of iron atoms (5000, 20000, 60000, 80000) are loaded into PSS-co-MA cages by a biomimetic synthesis method, and polymer PSS-co-MA coated iron oxide (Fe3O4) nanoparticles with an average core particle size of 4.4±1.2nm, 5.8±1.1nm, 7.9±2.2nm, and 9.0±2.2nm can be synthesized. Due to the cage structure formed by the self-assembly of polymer PSS-co-MA, the morphology of these nano-ions is well controlled, approximately spherical, and the shape factor (ratio of major axis to minor axis) is about 1.2. In addition, due to the average inner diameter of the cage formed by the self-assembly of polymer PSS-co-MA is 18.8±2.5nm, theoretically, with the increase of the number of iron atoms, iron oxide nanoparticles with a core particle size of about 20nm can be synthesized. Figure 3The biomimetic polymer PSS-co-MA coated iron oxide nanoparticles (PSS-co-MA) with different iron atom loadings synthesized in Example 2 are shown. 5000 、PSS-co-MA 20000 、PSS-co-MA 30000 、PSS-co-MA 60000 、PSS-co-MA 80000 The polymer encapsulates the iron oxide nanoparticles, and the weight ratio of the polymer to the iron oxide nanoparticles is between 1.1 and 3.6. Figure 4 The polymer PSS-co-MA coated iron oxide nanoparticles (PSS-co-MA) with different iron atom loadings synthesized in Example 2 are shown. 20000 、PSS-co-MA 80000 ) between pH 3 and 11. The hydrated particle size measured by dynamic light scattering showed that the core contained 20,000 iron atoms in the polymer-coated nanoparticles (PSS-co-MA 20000 ) and polymer-coated nanoparticles containing 80,000 iron atoms in the core (PSS-co-MA 80000 ) had no significant change in the hydrated particle size between pH 3 and 11, indicating that the aqueous solutions of these polymer-coated iron oxide nanoparticles were stable within this pH range. Figure 5 The stability of the polymer PSS-co-MA coated iron oxide nanoparticles synthesized in Example 2 under high concentration saline (API solution: 8wt% NaCl + 2wt% CaCl2) and high temperature conditions (90°C, 180°C) was shown. The hydrated particle size measured by dynamic light scattering showed that the core contained 5000 iron atoms of the polymer coated nanoparticle (PSS-co-MA 5000 ) The relative volume percentage of hydrated particle size did not change significantly within 48 hours, and it was stable under different pH conditions (pH 3-11) in the API solution. When placed at 90℃ and 180℃ for 48 hours, the relative volume percentage of hydrated particle size changed only slightly, which also shows that the polymer-coated nanoparticles can be stable in the API solution at 90℃ and 180℃. Figure 6 The biomimetic polymer PSS-co-MA coated iron oxide nanoparticles (PSS-co-MA) with different iron atom loadings synthesized in Example 2 are shown. 5000 、PSS-co-MA 20000 ,PSS-co-MA 60000 、PSS-co-MA 80000) isothermal remanent magnetization (IRM) acquisition curve and demagnetization curve (DCD) at 5k. The remanent magnetization coercivity obtained from the demagnetization curve is 99.68mT, 50.83mT, 47.61mT, 50.58mT, respectively, indicating that the mineral phase of the iron oxide nanoparticles is magnetite with low coercivity. Theoretically, when the intersection point of the isothermal remanent magnetization acquisition curve and the demagnetization curve is R = 0.5, the intersection point of the isothermal remanent magnetization acquisition curve and the demagnetization curve between these particles is between 0.34-0.42, indicating that these particles are well wrapped by the polymer and there is only a weak magnetic interaction between the particles. Figure 7 The biomimetic polymer PSS-co-MA coated iron oxide nanoparticles (PSS-co-MA 5000 、PSS-co-MA 20000 、PSS-co-MA 60000 、PSS-co-MA 80000 ) hysteresis loops at different temperatures. The hysteresis loop results at 2K show that all nanoparticles saturate at 300mT, with a coercivity of <60mT, indicating that their mineral composition is ferrimagnetic magnetite. As the number of iron atoms in the core increases, the saturation magnetization of the particles increases. The coercivity of all nanoparticles at 300K is basically zero, indicating that these particles are typical superparamagnetic nanoparticles. Fig. 9 The biomimetic polymer PSS-co-MA synthesized in Example 2 coated iron oxide nanoparticles (PSS-co-MA 5000 ) and the difference between the conventional ultrasonic chemical adsorption polymer PSS-co-MA coated iron oxide nanoparticles in the comparative example. (a) The biomimetic PSS-co-MA iron oxide nanoparticles can withstand a high temperature of 150°C for 24 hours in the API solution, while the PSS-co-MA iron oxide nanoparticles through ultrasonic chemical adsorption cannot withstand a high temperature of 150°C; (b) The biomimetic PSS-co-MA iron oxide nanoparticles have low adsorption to quartz sand in the API solution; (c) The biomimetic PSS-co-MA iron oxide nanoparticles can withstand a dilution concentration of 20ppm (0.002wt%) in the API solution, while the PSS-co-MA iron oxide nanoparticles through ultrasonic chemical adsorption cannot be stable at a dilution concentration of 20ppm (0.002wt%) in the API solution. Fig.10 The results show that the polymer PSS-co-MA coated iron oxide nanoparticles (PSS-co-MA) synthesized in Example 2 under different NaCl concentrations 5000 Optical and microscopic photographs of the emulsion formed by mixing 0.1 wt % (0.1 wt %) with dodecane.
[0092] Example 3. Preparation of polymer-coated manganese-doped and cobalt-doped iron oxide nanoparticles by biomimetic synthesis
[0093] All solutions were deoxygenated and placed in an anaerobic chamber. First, a mixture of ammonium ferrous sulfate (50 mM) and cobalt chloride (50 mM) was prepared with anaerobic deionized water, and then a solution of oxidant hydrogen peroxide (33.34 mM) was prepared with deionized water. In order to obtain a self-assembling polymer, 1 g of polystyrene sulfonate sodium-maleic acid copolymer (PSS-co-MA) polymer was dissolved in 1 L of 0.1 M NaCl solution until the final concentration was 1 mg / mL, and the pH value was adjusted to 8.5 with 0.5 M NaOH, and the temperature was controlled at 55 ° C for 10 min. In this way, the polymer began to self-assemble to form a cage structure under the conditions of salt ion concentration, pH value and temperature. Assuming that the cage structure of the polymer consists of 96 polymers with a molecular weight of approximately 1920000, a mixture of ammonium ferrous sulfate (50mM) and cobalt chloride (50mM) and a hydrogen peroxide (33.34mM) solution were added at a rate of 40 iron atoms and 40 cobalt atoms per cage per minute. Theoretically, 10,000 iron atoms and 10,000 cobalt atoms were added to each cage. In order to ensure that each cobalt-doped manganese iron oxide nanoparticle was completely encapsulated by the polymer cage, magnetic nanoparticles that were easy to assemble or difficult to encapsulate were removed at a centrifugal force of 10,000g, and the synthesized magnetic nanoparticles were concentrated using a molecular weight 100kD protein enrichment tube (amicon Ultra-12100kda), and the free polymer was removed to 30mg / mL for storage. Energy spectrum analysis was used to analyze whether cobalt was incorporated into the iron oxide nanoparticles.
[0094] Figure 8 The transmission electron microscopy (TEM) photo of the polymer PSS-co-MA coated cobalt-doped iron oxide nanoparticles synthesized in Example 3 (a) shows that the cobalt-doped iron oxide nanoparticles maintain good monodispersity due to the polymer encapsulation; (b) the particle size distribution shows that the average particle size of the cobalt-doped iron oxide nanoparticles is 5.6±1.3nm; (c) the electron microscope energy spectrum shows that the ratio of iron to cobalt in the polymer PSS-co-MA coated cobalt-doped iron oxide nanoparticles is 1:1, indicating that its composition may be Fe 1.5 Co 1.5 O4.
[0095] Example 4. Synthesis of Nanoparticle-Stabilized Oil-in-Water Nanoemulsion
[0096] First, CaCl2.2H2O was dissolved in a separate container at a concentration of 5 M. Using a 20 ml glass vial, 16.2 ml of PSS-co-MA prepared in Example 1 at a concentration of 1.23 wt% was added. 5000Iron oxide nanoparticles, 0.8 ml of 5 M CaCl2 solution and 3 ml of octadecene. The vial was fixed in a 400 ml beaker with a foam holder, cooled in an ice bath and sonicated for a total of 10 minutes at a 30 sec / 30 sec 50% amplitude setting. The solution was further centrifuged at 3000 rpm to separate into three layers. The middle layer was taken to obtain a stable nanoemulsion, and the upper and lower layers were discarded to remove free oil and free nanoparticles, respectively.
[0097] Fig.12 The nanoemulsion formed by mixing polymer PSS-co-MA coated iron oxide nanoparticles with octadecene and 0.2M calcium chloride is shown in Example 4. Only when the concentration of polymer coated iron oxide nanoparticles in the entire water-oil system is greater than 0.8wt% can a uniform nanoemulsion be completely formed without stratification. Fig.13 The two-dimensional and three-dimensional laser confocal microscopy, cryo-scanning electron microscopy, atomic force microscopy, and X-ray scanning transmission microscopy images of the nanoemulsion formed by Example 4 are shown. The two-dimensional and three-dimensional laser confocal microscopy images show that the nanoparticles (PSS-co-MA) are encapsulated by the polymer. 5000 , 1wt%) is a typical oil-in-water nanoemulsion, and the nano-oil droplets are monodispersed in the salt solution; atomic force microscopy shows that the surface of the nano-oil droplets is covered with nanoparticles; oxygen-edge and iron-edge X-ray scanning transmission imaging shows that the oil-water interface of the nano-oil droplets is covered by polymer-coated iron oxide nanoparticles and is stabilized in 0.2M calcium chloride solution. Fig.14 The relationship between the hydrated particle size and the storage time and temperature of the nanoemulsion formed in Example 4 measured by dynamic light scattering is shown. The results show that the hydrated particle size measured after the nanoemulsion is stored in a 0.2M calcium chloride high salt solution for 56 hours is only slightly changed and there is no significant difference with the hydrated particle size after storage for 7 days. In addition, there is no significant difference in the hydrated particle size distribution diagram at 25°C and 90°C after storage for 7 days, indicating the long-term stability of the synthesized nanoemulsion.
[0098] Example 5. Synthesis of oil-in-water composite nanoemulsion containing a single oil component and multiple metal ions
[0099] First, prepare a high concentration of mixed solution containing different metal ions. Weigh 3.68g CaCl2.2H2O, 3.64g Co(NO3)2﹒6H2O and 2.97g NiCl2﹒2H2O and dissolve them in 10mL water to prepare a final concentration of 2.5M CaCl2.2H2O, 1.25M Co(NO3)2﹒6H2O and 1.25M NiCl2﹒2H2O. In another separate glass bottle, add 1.3wt% of PSS-co-MA prepared in Example 1. 500015.4mL of iron oxide nanoparticles, 1.6mL of metal ion mixture and 3mL of octadecene were fixed in a 400ml beaker with a foam holder in an ice bath and ultrasonicated for 10 minutes at 30s / 30s 50% amplitude. In order to prepare composite nanoemulsions of other single oil components, other oils such as dodecane, mineral oil and silicone oil can be used instead of octadecene. The solution was further separated into three layers by centrifugation at 3000 rpm. The middle layer was extracted to obtain a stable nanoemulsion, and the upper and lower layers were discarded to remove free oil and free nanoparticles respectively.
[0100] Fig.21 a-21f shows the cryo-SEM (a), AFM (b), (c) oxygen-edge X-ray scanning transmission microscopy images, (d) hydrated particle size distribution and (e, f) energy spectra of the composite nanoemulsion prepared by Example 5. The cryo-SEM, AFM and oxygen-edge X-ray scanning transmission electron microscopy images clearly show that a nanodroplet of a composite nanoemulsion is composed of multiple even smaller nanodroplets; the hydrated particle size distribution shows that the hydrated particle size of the composite nanoemulsion is between 80 and 300 nm; compared with the energy spectrum of the surrounding aqueous solution, the energy spectrum of the nanodroplets of the composite nanoemulsion contains more carbon, iron, calcium, cobalt and nickel elements, indicating that a variety of metal ions combined with polymer-coated nanoparticles exist at the oil-water interface of the composite nanoemulsion.
[0101] Example 6. Synthesis of oil-in-water composite nanoemulsion containing multiple oil components and multiple metal ions
[0102] First, prepare a high concentration of mixed solution containing different metal ions. Weigh 3.68g CaCl2.2H2O, 3.64g Co(NO3)2﹒6H2O and 2.97g NiCl2﹒2H2O and dissolve them in 10mL water to prepare a final concentration of 2.5M CaCl2.2H2O, 1.25M Co(NO3)2﹒6H2O and 1.25M NiCl2﹒2H2O. In another separate glass bottle, add 1.3wt% of PSS-co-MA prepared in Example 1. 5000 15.4 mL of iron oxide nanoparticles, 1.6 mL of metal ion mixture, 1 mL of octadecene, 1 mL of mineral oil and 1 mL of silicone oil were fixed in a 400 ml beaker with a foam holder in an ice bath and ultrasonicated for 10 minutes at 30s / 30s 50% amplitude. The solution was further centrifuged at 3000 rpm to separate into three layers. The middle layer was taken to obtain a stable nanoemulsion, and the upper and lower layers were discarded to remove free oil and free nanoparticles, respectively.
[0103] Fig. 22a-22h shows the cryo-SEM images (a, c), size distribution (b), energy spectrum (d), atomic force microscopy (e) and oxygen edge, iron edge, benzene ring edge X-ray scanning transmission X-ray microscopy images (fh) of the composite nanoemulsion prepared by Example 6. The cryo-SEM image (a) shows that the nano-oil droplets are monodispersed in the aqueous solution; the high-resolution cryo-SEM image (c) and the atomic force microscopy image (e) show that the nano-droplets of the entire nano-emulsion are composed of multiple nano-oil droplets with smaller particle sizes, darker colors and lighter colors, among which the energy spectrum (d) of the darker small nano-oil droplets shows that it contains a high concentration of silicon, indicating that it is silicone oil, and the lighter oil droplets are octadecene and mineral oil of hydrocarbons. The oxygen edge, iron edge, benzene ring edge X-ray scanning transmission X-ray microscopy images (fh) show that the polymer-coated nanoparticles are present at the oil-water interface of the composite nano-emulsion.
[0104] Example 7. Synthesis of oil-in-water composite nanoemulsion containing multiple oil components, multiple metal ions and cationic surfactants
[0105] First, the cationic surfactant dodecyltrimethylammonium bromide (DTAB) was dissolved in another separate container at a concentration of 10 mg / mL. Then, a high concentration of a mixed solution containing different metal ions was prepared in another container. 3.68 g of CaCl2.2H2O, 3.64 g of Co(NO3)2﹒6H2O and 2.97 g of NiCl2﹒2H2O were weighed and dissolved in 10 mL of water to prepare a final concentration of 2.5 M CaCl2.2H2O, 1.25 M Co(NO3)2﹒6H2O and 1.25 M NiCl2﹒2H2O. In a separate glass bottle, 1.3 wt% of PSS-co-MA prepared in Example 1 was added. 5000 15.2 mL of iron oxide nanoparticles, 0.2 mL of DTAB solution (10 mg / mL), 1.6 mL of metal ion mixture, 1 mL of octadecene, 1 mL of mineral oil and 1 mL of silicone oil, the vial was fixed in an ice bath in a 400 mL beaker with a foam holder, and ultrasonicated for 10 minutes at 30s / 30s 50% amplitude. The solution was further centrifuged at 3000 rpm to separate into three layers. The middle layer was extracted to obtain a stable nanoemulsion, and the upper and lower layers were discarded to remove free oil and free nanoparticles, respectively.
[0106] Fig.23 a-23d shows the (a, b) cryo-scanning electron microscope image, (c) atomic force microscope image and (d) structural schematic diagram of the water-in-oil composite nanoemulsion containing multiple oil components, multiple metal ions and cationic surfactants prepared by Example 7.
[0107] Example 8. Synthesis of oil-in-water composite nanoemulsion containing multiple oil components, multiple metal ions and anionic surfactants
[0108] First, dissolve the anionic surfactant sodium dodecyl sulfate (SDS) in another separate container at a concentration of 10 mg / mL. Then use another container to prepare a high concentration of a mixed solution containing different metal ions. Weigh 3.68g CaCl2.2H2O, 3.64g Co(NO3)2﹒6H2O and 2.97g NiCl2﹒2H2O and dissolve them in 10mL water to prepare a final concentration of 2.5M CaCl2.2H2O, 1.25M Co(NO3)2﹒6H2O and 1.25M NiCl2﹒2H2O. Add 1.3wt% of PSS-co-MA prepared in Example 1 into a separate glass bottle. 5000 15.2 mL of iron oxide nanoparticles, 0.2 mL of DTAB solution (10 mg / mL), 1.6 mL of metal ion mixture, 1 mL of octadecene, 1 mL of mineral oil and 1 mL of silicone oil, the vial was fixed in an ice bath in a 400 mL beaker with a foam holder, and ultrasonicated for 10 minutes at 30s / 30s 50% amplitude. The solution was further centrifuged at 3000 rpm to separate into three layers. The middle layer was extracted to obtain a stable nanoemulsion, and the upper and lower layers were discarded to remove free oil and free nanoparticles, respectively.
[0109] Fig.24 a-24c shows the cryo-scanning electron microscope image (a), atomic force microscope image (b) and structural schematic diagram (c) of the composite nanoemulsion containing anionic surfactant prepared by Example 8, in which the oil phase nanodroplets are composed of sodium dodecyl sulfate (SDS) anionic surfactant, PSS-co-MA iron oxide nanoparticles combined with calcium ions, nickel ions and cobalt ions, octadecene, mineral oil and silicone oil nanodroplets.
[0110] Example 9. Application of nanoemulsion to prepare stable macroemulsion
[0111] In order to prepare nano droplet stable large emulsion and compare with the emulsion stable with nanoparticle, add 10mL stabilizing agent and 10mL octadecene respectively in bottle, stabilizing agent is respectively PSS-co-MA coated iron oxide nanoparticles prepared by embodiment 2, polymer PSS-co-MA coated iron oxide nanoparticles and CaCl prepared by embodiment 2 composite (CaCl after composite concentration is 0.2M) of solution, nanoemulsion prepared by embodiment 4, nanoemulsion prepared by embodiment 4 and CaCl composite (CaCl after composite concentration is 0.2M).Then medium intensity homogenizer is used that oil, water and nanoemulsion in bottle are homogenized to obtain large emulsion in 2 minutes.Adjust the consumption of PSS-co-MA coated iron oxide nanoparticles and nanoemulsion so that in final gained large emulsion, the concentration of polymer PSS-co-MA coated iron oxide nanoparticles is 0.001-0.01wt%.Gained large emulsion normal temperature is left on the desktop, and continuous observation 58 days sees whether there is demulsification phenomenon. In order to further compare the difference between polymer-coated nanoparticles and nanoemulsions in stabilizing macroemulsions, the macroemulsions prepared above were stored at room temperature, and the hydrated particle size distributions were measured for 56 hours and 6 days using a dynamic light scattering instrument, and the dynamic rheological data of each emulsion were further measured using a rheometer under fixed frequency conditions after 7 days of storage. In addition, macroemulsions can also be prepared by synthesizing stable water-in-oil nanoemulsions using co-surfactants and metal ions, and the preparation process is similar to the above process.
[0112] Fig.15 The results of Example 9 show that different low concentrations (0.001-0.01 wt%) of polymer-coated iron oxide nanoparticles (PSS-co-MA 5000 ) aqueous solution, salt solution (0.2M CaCl2) of polymer-coated iron oxide nanoparticles, aqueous solution of polymer-coated iron oxide nanoparticles stabilizing nanodroplets, and salt solution (0.2M CaCl2) of nanodroplets are stored at room temperature for 38 days. Compared with polymer-coated iron oxide nanoparticles, the emulsion formed from the nanodroplet salt solution only needs a nanoparticle concentration of 0.002-0.01wt% to synthesize a stable emulsion. The upper layer emulsion synthesized under this concentration condition is uniform in texture and has no obvious demulsification phenomenon. The upper layer emulsion formed by the nanodroplet aqueous solution is stable under the nanoparticle concentration condition of 0.004-0.01wt%. However, the emulsions stable under this concentration condition of nanoparticle aqueous solution or salt solution show obvious demulsification phenomenon. The upper layer emulsions formed by nanoparticle aqueous solutions of different concentrations have shown the phenomenon of oil-water separation, and the nanoparticles are mainly present in the lower layer of the aqueous solution; while the emulsions formed by nanoparticle salt solutions of different concentrations have shown obvious demulsification, and the emulsions show the brown color of iron oxide nanoparticles and have obvious uneven texture.
[0113] Fig.16 It is shown that by Example 9, the polymer PSS-co-MA coated iron oxide nanoparticles (PSS-co-MA 5000 ) salt solution (0.2M CaCl2), nanodroplet water solution, and nanodroplet salt solution (0.2M CaCl2) rheological data of emulsions formed. The storage modulus G' of all emulsions synthesized with nanoparticles or nanodroplets is greater than the loss modulus G", indicating that all synthesized emulsions can form a gel-like structure. In addition, the storage modulus G' and loss modulus G" of the emulsion formed in the nanodroplet salt solution are greater than the emulsion formed in the single nanoparticle salt solution, indicating that nanodroplets are a better emulsifier than single nanoparticles.
[0114] Fig.17 Comparison of the polymer PSS-co-MA coated iron oxide nanoparticles (PSS-co-MA 5000 ) salt solution (0.2M CaCl2), nanodroplet water solution, and nanodroplet salt solution (0.2M CaCl2) changes in hydrated particle size after storage for 56 hours and 6 days. The results show that extremely low concentration (0.002wt% and 0.006wt%) of nanodroplet salt solution can stabilize the emulsion well, so that the relative volume percentage of the hydrated particle size of the emulsion does not change significantly within 6 days. However, the emulsion synthesized by 0.006wt% nanodroplet water solution and nanoparticle salt solution has obvious changes in hydrated particle size within 6 days. Only when the concentration of nanodroplet water solution is increased to 0.1wt% can the large emulsion be stabilized, which shows that metal calcium ions are also a good synergistic stabilizer and play a vital role in the process of preparing stable emulsions using nanodroplet salt solution. Even if the concentration of polymer-coated iron oxide nanoparticle salt solution is increased to 0.1wt%, it cannot stabilize the large emulsion well, and its hydrated particle size changes significantly between 56 hours and 6 days.
[0115] Fig.18The microstructure of the emulsion prepared in Example 9 with 0.01 wt% nanodroplet salt solution (0.2M CaCl2) is shown. (ab) Two-dimensional and three-dimensional laser confocal (scale bar 5 μm) photos of the emulsion show that the nanodroplets react with the oil to generate nanodroplets and microdroplets with larger particle sizes (diameter 736nm-3.4μm) covering the surface of the emulsion, greatly enhancing the specific surface area of the emulsion; in addition, nanodroplets of about 200 nanometers can be seen on the surface of the microdroplets, indicating that the microdroplets covering the surface of the emulsion are also stabilized by nanodroplets; (c) Oxygen edge X-ray scanning transmission microscopy imaging of the emulsion also shows that the nanodroplets with larger particle sizes are formed. Droplets and micron droplets cover the surface of the emulsion, and there is an obvious oil-water interface (high oxygen content) between the nanodroplets and micron oil droplets and the large oil droplets in the emulsion; (dg) are X-ray scanning transmission electron microscopy images of the oxygen edge, iron edge, calcium edge and benzene ring edge of the interface structure between the nanodroplets and the large oil droplets in the emulsion, respectively. It is found that there is a high content of oxygen, iron, calcium and benzene ring at the interface between the nanodroplets and the large oil droplets in the emulsion, indicating that the polymer-coated iron oxide nanoparticles bound to calcium ions are the bridge connecting the nanodroplets, micron droplets and the emulsion oil droplets.
[0116] Fig.19 The low-temperature scanning electron microscope and energy dispersive spectroscopy (EDX) analysis images of the emulsion prepared by Example 9 and made of nanodroplet salt solution (0.2M CaCl2) are shown, indicating that many calcium and iron elements accumulate at the interface, and the calcium ions are a synergistic stabilizer, forming a shell surrounding the entire emulsion oil droplet.
[0117] Fig. 20 It is shown that the high concentration of Na + 、Ni 2+ 、Co 2+ and Fe 3+ Stable oil-in-water emulsions of ) can also be prepared by nanoemulsions with other monovalent, divalent and trivalent metal ions.
[0118] Example 10
[0119] A macroemulsion was prepared according to the same operation and conditions as in Example 9, with the nanoemulsion prepared in Example 4 and CaCl2 compounded (the CaCl2 concentration after compounding was 0.2 M) as a stabilizer, except that the 0.2 M CaCl2 solution was replaced by 0.2 M NaCl, 1 M NaCl, 0.2 M NiCl2, and 0.2 M FeCl3, respectively.
[0120] Embodiment 11
[0121] A large emulsion was prepared according to the same operation and conditions as in Example 9, except that the water-in-oil composite nanoemulsion containing a single oil component and multiple metal ions prepared in Example 5 and CaCl2 (the concentration of CaCl2 after compounding was 0.2M) were used as a stabilizer, and the concentration ratios of the polymer PSS-co-MA coated iron oxide nanoparticles in the composite nanoemulsion were 0.0002wt%, 0.0003wt%, 0.0004wt%, and 0.0005wt%.
[0122] Fig.25 The photographs are shown after 48 hours of synthesizing the emulsion prepared by Example 11 using different concentrations of water-in-oil composite nanoemulsions containing multiple oil components and multiple metal ions. It is found that the composite nanoemulsion requires a lower concentration of polymer-coated iron oxide nanoparticles to stabilize the emulsion than the simple nanoemulsion, and the lowest concentration can reach 0.0002wt%.
[0123] Comparative Example 1. Polymer is non-covalently adsorbed on the surface of iron oxide nanoparticles by ultrasonic method. 300 ml of MiliQ water is poured into a 400 ml clean beaker, and 12 grams of PSS-co-MA polymer is dissolved in water. Concentrated hydrochloric acid is added to adjust the pH value of the polymer solution to 5. Stir for 10 minutes with a stirring bar of appropriate size. Then 3g of Fe3O4 particles (20-30nm, American Research Nanomaterials Company) are added to the solution and ultrasonically treated in an ice bath for 60 minutes at a 50% amplitude setting. In order to remove aggregated nanoparticles, the ultrasonically treated solution is centrifuged at 4000g for 20 minutes. Finally, the supernatant is concentrated and free polymer is removed to 30mg / mL using a 100kD protein enrichment tube (amicon Ultra-12, 100kDa) for storage. The iron content and polymer content in the nanoparticles were determined by inductively coupled plasma mass spectrometry (ICP-MS) and thermogravimetric analysis (TGA).
[0124] Example 12. Real-time observation of the displacement effect of nanoemulsion on residual oil using a microscopic displacement system
[0125] In order to observe the dynamic interaction between nanoemulsion and oil without adding metal ions, the glass micromodel was first saturated with water using a syringe pump at an injection rate of 15uL / min. Then 1-octadecene was injected into the micromodel at an injection rate of 5ul / min until the oil saturation state was reached. Water was injected at a rate of 5 microliters per minute for the first water displacement until no oil was produced in the effluent. A single pore volume of nanoemulsion (concentration 0.01wt%) was injected into the micromodel, and real-time imaging was performed using a laser confocal microscope to study the interaction between the nanoemulsion and the residual oil and the crude oil recovery rate to evaluate the displacement effect of the residual oil.
[0126] To observe the interaction of nanoemulsion with oil in saline solution containing metal ions, the glass micromodel was first saturated with 0.2 m calcium chloride solution using a syringe pump at an injection rate of 15 μL / min. 1-Octadecene was then injected into the micromodel at an injection rate of 5 μL / min until the syngas saturation condition was reached. 0.2 M CaCl2 solution was injected at a rate of 5 microliters per minute until no more oil was produced in the effluent. Nano-oil droplets at a concentration of 0.01 wt% and 0.2 m CaCl2 were injected into the micromodel and imaged using a confocal microscope to study the interaction and displacement effect of the nanoemulsion with the residual oil.
[0127] Fig.26 a-26c shows the displacement effect of nanoemulsion on residual oil and its dynamic interaction with oil using laser confocal microscopy and a two-dimensional displacement micromodel (a) and a three-dimensional micromodel made of quartz sand (b) through Example 12. The results show that the nanoemulsion can gather at the oil-water interface of the residual oil, displacing the residual oil to form a microemulsion and a macroemulsion (c) with larger particle size.
[0128] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A polymer-coated nanoparticle, wherein the polymer self-assembles into a cage-like structure to coat the nanoparticle; the chemical structure of the nanoparticle is Fe (3-x) M x O4, 0≤x<3 or Fe (2-x) M x O3, 0≤ x <2, where The M is selected from Mn, Cu, Zn, Ni, Gd or Co; the size of the nanoparticles is 5-150nm; the polymer contains sulfonic acid groups and carboxyl groups, and the sulfonic acid groups and carboxyl groups can be fully or partially converted into salt forms, and the salt is potassium salt, sodium salt, ammonium salt; the polymer is obtained by copolymerizing an unsaturated monomer containing a sulfonic acid group and an unsaturated monomer containing a carboxyl group; the unsaturated monomer containing a sulfonic acid group is selected from styrene sulfonate, methyl propylene sulfonate, propylene sulfonate, vinyl sulfonate, butylene sulfonate, 2-acrylamide- 2-Methylpropane sulfonate; the unsaturated monomer containing a carboxyl group is selected from maleic acid, acrylic acid, methacrylic acid, crotonic acid, 2-ethylacrylic acid, 2-pentenoic acid, 4-pentene, 2-octenoic acid, 3-vinylbenzoic acid, 4-vinylbenzoic acid, 10-undecenoic acid, erucic acid, brassinoic acid, palmitoleic acid, oleic acid, nervonic acid, linolenic acid, ricinoleic acid, 4-oxo-4-phenyl-2-butenoic acid, 2-bromoacrylic acid, 2-bromomethyl-acrylic acid, sorbic acid, itaconic acid, citraconic acid, fumaric acid, methylfumaric acid, mesaconic acid, and mucofuric acid.
2. The nanoparticle according to claim 1, characterized in that The molecular weight of the polymer is 1-3 million.
3. The nanoparticle according to claim 1, characterized in that The molecular weight of the polymer is 1.5-2 million.
4. The nanoparticles according to claim 1, characterized in that The polymer is a sodium salt of poly(4-styrene sulfonic acid-maleic acid copolymer), wherein the quantity ratio of sulfonate to carboxyl in the polymer is 1:2, and the molecular weight is 1.5-2 million.
5. The nanoparticle according to claim 1, characterized in that The size of the metal oxide nanoparticles is 10-20 nm.
6. The nanoparticle according to claim 1, characterized in that The metal oxide nanoparticles are Fe3O4, Fe 1.5 Co 1.5 O4.
7. The nanoparticle according to claim 1, characterized in that Each polymer cage contains a nanoparticle, and a single nanoparticle in the cage has 1,000-120,000 metal atoms; the metal atoms are iron.
8. The nanoparticle according to claim 7, characterized in that Each polymer cage has 5,000-10,000 metal atoms.
9. The method for preparing the nanoparticles according to any one of claims 1 to 8, comprising the following steps: a) allowing the polymer to self-assemble to form a cage structure; b) adding metal salts and oxidants to grow nanoparticle crystals in the cavity of the cage structure formed by the polymer; optionally, a purification step (c) is also performed: after centrifugation, the synthesized nanoparticles are concentrated using a protein enrichment tube.
10. The preparation method according to claim 9, characterized in that: The conditions for the polymer to self-assemble into a cage-like structure are a salt concentration of 0.05-1M halide salt, a pH value of 3-10, a temperature of 45-90° C., and a polymer concentration of 0.25-5 mg / mL.
11. The preparation method according to claim 10, characterized in that: The conditions for the polymer to self-assemble into a cage-like structure are a salt concentration of 0.1-0.2 M, a pH value of 5-8.5, a temperature of 50-60° C., and a polymer concentration of 1-2 mg / mL.
12. The preparation method according to claim 10, characterized in that: The pH value is 7-8.5 and the temperature is 50-55℃.
13. The preparation method according to claim 9, characterized in that: The metal salts include iron salts.
14. The preparation method according to claim 13, characterized in that: A salt of a metal M is also added, wherein the metal M is selected from at least one of Mn, Cu, Zn, Ni, Gd, and Co.
15. The preparation method according to claim 13, characterized in that: The salt of the metal M is a halide salt.
16. The preparation method according to claim 13, characterized in that: The salt of the metal M is selected from manganese chloride, copper chloride and cobalt chloride.
17. The preparation method according to claim 9, characterized in that: The molar ratio of the metal salt to the oxidant is 2-3:
1.
18. The preparation method according to claim 9, characterized in that: The metal salt is added at a rate of 10-200 metal ions per minute per polymer in the system.
19. The preparation method according to claim 18, characterized in that: The metal salt is added at a rate of 80-120 metal ions per minute per polymer in the system.
20. A composite nanoemulsion comprising: a) a continuous phase; b) a discontinuous phase; c) a stabilizer; d) metal ions, wherein the stabilizer comprises the polymer-coated nanoparticles according to any one of claims 1 to 8 or the polymer-coated nanoparticles prepared by the preparation method according to any one of claims 10 to 19.
21. The composite nanoemulsion according to claim 20, characterized in that The particle size of the composite nanoemulsion is 20-1000 nm.
22. The composite nanoemulsion according to claim 21, characterized in that The particle size of the composite nanoemulsion is 100-600 nm.
23. The composite nanoemulsion according to claim 20, characterized in that The continuous phase is a polar solvent selected from water, alcohol and nitriles; the polar solvent is added alone or in the form of a solvent in a stabilizer solution; and / or The discontinuous phase is an oil that is incompatible with the continuous phase.
24. The composite nanoemulsion according to claim 23, characterized in that The discontinuous phase is at least one of unsaturated fatty acid, mineral oil, fatty oil and silicone oil.
25. The composite nanoemulsion according to claim 20, characterized in that The ratio of the volume of the discontinuous phase to the volume of the continuous phase is from 0.15 to less than 1.
26. The composite nanoemulsion according to claim 25, characterized in that The ratio of the volume of the discontinuous phase to the volume of the continuous phase is 0.18-0.
3.
27. The composite nanoemulsion according to claim 20, characterized in that The concentration of the polymer-coated nanoparticles in the nanoemulsion is 0.2-2 wt %.
28. The composite nanoemulsion according to claim 27, characterized in that The concentration of the polymer-coated nanoparticles in the nanoemulsion is 0.8-1.2 wt %.
29. The composite nanoemulsion according to claim 20, characterized in that The stabilizers include anionic surfactants and cationic surfactants.
30. The composite nanoemulsion according to claim 20, characterized in that The metal ions are monovalent or multivalent ions; the concentration of the metal ions in the system is 0.1-0.3M.
31. The composite nanoemulsion according to claim 30, characterized in that The metal ion is Na + , K + , Ca 2+ ,Co 2 + , Ni 2+ , Ba 2+ ,Mg 2+ , Al 3+ , Cu 2+ At least one of .
32. A method for preparing the composite nanoemulsion according to any one of claims 20 to 31, comprising the following steps: A) adding a continuous phase, a stabilizer, metal ions and a discontinuous phase for mixing, wherein the stabilizer comprises the polymer-coated nanoparticles according to any one of claims 1 to 8 or the polymer-coated nanoparticles prepared by the preparation method according to any one of claims 9 to 19; B) centrifugation to separate and take the middle layer of emulsion as the composite nanoemulsion.
33. A macroemulsion comprising a) a continuous phase, b) a discontinuous phase; c) a stabilizer, wherein the stabilizer comprises the composite nanoemulsion according to any one of claims 20 to 30.
34. The macroemulsion of claim 33, wherein The continuous phase is a polar solvent selected from water, alcohol and nitriles; the discontinuous phase is an oil incompatible with the continuous phase.
35. The macroemulsion of claim 34, wherein The discontinuous phase is at least one of unsaturated fatty acid, mineral oil, fatty oil and silicone oil.
36. The macroemulsion of claim 34, wherein The ratio of the volume of the discontinuous phase to the volume of the continuous phase is 0.5-3.
37. The macroemulsion of claim 36, wherein The ratio of the volume of the discontinuous phase to the volume of the continuous phase is 1-2.
38. The macroemulsion of claim 33, wherein: The concentration of polymer-coated nanoparticles is 0.001-0.01wt%.
39. A method for preparing a macroemulsion according to any one of claims 33 to 38, comprising the following steps: The prepared composite nanoemulsion, the continuous phase and the discontinuous phase are uniformly mixed to obtain a macroemulsion.
40. Use of the composite nanoemulsion according to any one of claims 20 to 30 for drug delivery, in situ or in vivo imaging, displacement of residual petroleum or catalysis.
Citation Information
Patent Citations
Surface-Active Polymer and Its Use in a Water-in-Oil Emulsion
US20080250701A1
Preparation method of monodisperse magnetic human ferritin
CN102115746A
Animal magnetic ferritin material and its preparation method
CN102464715A
Ferritin nanometer material for displaying antibody and preparing method and application of ferrtin nanometer material
CN110272500A
Preparation method and application of heat-resistant ferritin
CN110819651A